Post-exercise hypotension and cardiovascular responses to moderate orthostatic stress in endurance-trained males - Scott, J. M.; Esch, B. T. A.; Lusina, S.-J. C.; McKenzie, D. C.; Koehle, M. S.; Sheel, A. W.; Warburton, D. E. R. (Applied Physiology, Nutrition, and Metabolism, 2008)
Abstract: We tested the hypothesis that following an acute bout of exercise cardiovascular and cerebrovascular responses to lower-body negative pressure (LBNP) would be altered due to post-exercise hypotension (PEH). Ten healthy, male, endurance-trained athletes (mean age ± SD = 29.6 ± 5) were assessed for cardiovascular and cerebrovascular responses to LBNP following acute bouts of interval and continuous exercise. Mean arterial pressure (MAP), cardiac output, total peripheral resistance, heart rate variability, and total cerebral oxygen index were determined during a baseline LBNP session. These indices were also determined during two other LBNP sessions: following an acute bout of interval exercise, and following an acute bout of continuous exercise. Compared with baseline, MAP was reduced after both exercise conditions, similar to values previously reported (10 mmHg; p < 0.05 vs. pre-exercise). Total peripheral resistance was significantly reduced following both exercise bouts, and heart rate was significantly increased post-exercise (rest: 59.6 ± 11.2; interval: 77.8 ± 12.8; continuous: 80.3 ± 15.2 beats/min). Both cardiac output and stroke volume responses to LBNP following exercise were not altered when compared with baseline measurements. Tissue oxygenation during -40 mmHg (interval: 74.31% ± 7.82% vs. continuous: 69.13% ± 5.23%) was significantly lower than during normobaric pressure (interval: 77.14% ± 1.30% vs. continuous: 74.41% ± 0.94%). It appears from these observations that although young, endurance-trained males experience PEH following acute bouts of interval or continuous exercise, this hypotension does not alter the cardiovascular and cerebrovascular responses to a moderate orthostatic stress.